Research on the impact of environmental regulation on water resources utilization efficiency in China based on the SYS-GMM model - X. B. Wang (IWA Publishing, 2021)
The paper uses the super-efficiency data envelopment analysis (DEA) model to measure the water resources utilization efficiency of 30 provinces in China, and then uses the system generalized method of moments (GMM) model to analyze the impact of environmental regulations on China's regional water resources utilization efficiency. Conclusions as follows. (1) The overall water utilization efficiency is low, and the regions are very unbalanced. The more efficient areas are concentrated in the east, and the less efficient areas are in the west. (2) There is a ‘U’-shaped relationship between the intensity of environmental regulation and water resource utilization efficiency, that is, weaker environmental regulation intensity is not conducive to the improvement of water resource utilization efficiency, but when the intensity of environmental regulation crosses the ‘inflection point’, it can promote the improvement of water resources utilization efficiency. (3) The level of economic development has a very significant positive effect on water resources utilization efficiency, and the coefficient of scientific and technological progress is positive, but the impact of scientific and technological input on water resources utilization efficiency is limited and not significant; industrial structure and water resource utilization efficiency shows a negative correlation; water use structure and water resources efficiency show a negative correlation. HIGHLIGHTS Measure the efficiency of water resources based on super-efficiency DEA.; Use SYS-GMM to verify the impact of environmental regulations on water resources efficiency.; Obtain recommendations that help improve water efficiency.;